2021
DOI: 10.1101/2021.10.12.464071
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping tumor spheroid mechanics in dependence of 3D microenvironment stiffness and degradability by Brillouin microscopy

Abstract: Altered biophysical properties of cancer cells and of their microenvironment contribute to cancer progression. While the relationship between microenvironmental stiffness and cancer cell mechanical properties and responses has been previously studied using two-dimensional (2D) systems, much less is known about it in a physiologically more relevant 3D context and in particular for multicellular systems. To investigate the influence of microenvironment stiffness on tumor spheroid mechanics, we first generated MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 63 publications
2
2
0
Order By: Relevance
“…Much of the previous work studying ERK and YAP activity in response to stiffness-and functional consequences therein-have been conducted in cells on 2D surfaces, often at non-physiological stiffnesses (>100 kPa), and which do not recapitulate the 3D environment in solid tumors. Our data agrees with other studies demonstrating that increased 3D collagen stiffness can suppress proliferation and invasion in other cancer types (Berger et al, 2017;Staneva et al, 2018;Berger et al, 2020;Mahajan et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…Much of the previous work studying ERK and YAP activity in response to stiffness-and functional consequences therein-have been conducted in cells on 2D surfaces, often at non-physiological stiffnesses (>100 kPa), and which do not recapitulate the 3D environment in solid tumors. Our data agrees with other studies demonstrating that increased 3D collagen stiffness can suppress proliferation and invasion in other cancer types (Berger et al, 2017;Staneva et al, 2018;Berger et al, 2020;Mahajan et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the spheroids also appeared to spread away from the tumor mass, presenting a less compact structure following a 5-day culture within the 3D collagen matrix. Our observations align with Mahajan and colleagues' study, where increased stiffness of degradable hydrogel (15-20 kPa) similarly reduces the growth of MCF7 spheroids, accompanied by lower invasion into the matrix (Mahajan et al, 2021). Our further investigation revealed that changes in spheroid sizes and morphologies appeared to be regulated by cell growth, cell cycle arrest, apoptosis, and EMT when embedded in collagen matrices.…”
Section: Discussionsupporting
confidence: 91%
“…For imaging purposes of TME, nonlinear imaging like multiphoton microscopy and second harmonic generation can be used, especially for live imaging of composition and architecture change of the TME. As a noncontact method, Brillouin microscopy is used to map the stiffness of different biological samples in 2D and 3D. Since Brillouin microscopy is a noninvasive measurement technique, it can potentially be adapted for obtaining in vivo measurements of tissue mechanical properties with subcellular resolution. Other noninvasive methods such as magnetic resonance elastography, ultrasonography, and optical coherence tomography , are also widely used in measuring the mechanical properties of both healthy normal and cancer tissues in vivo since they are based on elastography. One of the most commonly used stiffness measurement techniques for biomaterials or synthetic materials in biomedical research is shear rheometry.…”
Section: Extracellular Matrixmentioning
confidence: 99%